Melatonin in Male Dromedary Camel (Camelus dromedarius) Seminal Plasma and Its Specific MT1 and MT2 Receptors on Sperm Membranes - Lamia Doghbri; Melissa Carvajal-Serna; Moufida Atigui; Adriana Casao; Victoria Peña-Delgado; Mabrouk-Mouldi Seddik; Mohamed Dbara; Rosaura Pérez-Pé; Mohamed Hammadi (Animals)
Camels (Camelus dromedarius) are seasonal short-day breeders, regulated by photoperiod and melatonin secretion. However, no studies have explored melatonin levels in camel seminal plasma or their relationship with testosterone, age, or climatic factors, nor is it known whether melatonin receptors exist in camel spermatozoa to respond to seminal melatonin. This study aimed to analyze melatonin levels in camel seminal plasma and its specific receptors in spermatozoa. Semen samples were obtained from November to March (breeding season). Testosterone and melatonin levels were measured in seminal plasma by ELISA. Melatonin receptors were localized in spermatozoa using immunofluorescence, and their presence was confirmed by Western Blot. Melatonin levels were higher from November to January and decreased in February and March. No correlation between testosterone and melatonin levels was found, but both hormones were negatively correlated with daylength (p = 0.0089 and p = 0.0688, respectively). Testosterone, but not melatonin, levels were affected by age. Two melatonin receptors (MT1, MT2) were detected on camel spermatozoa, with several immunotypes labeled mainly in the tail and post-acrosome region, but also in the acrosome and neck. Western Blot analysis confirmed the presence of these receptors, showing a 39 kDa band for MT1 and a 36 kDa band for MT2. Understanding melatonin’s effects on sperm could help ejaculates’ processing procedures, semen handling, and infertility issues in camels.